2004
DOI: 10.1124/dmd.32.4.382
|View full text |Cite
|
Sign up to set email alerts
|

A Proteomic Approach to the Identification of Cytochrome P450 Isoforms in Male and Female Rat Liver by Nanoscale Liquid Chromatography-Electrospray Ionization-Tandem Mass Spectrometry

Abstract: ABSTRACT:Nanoscale reversed-phase liquid chromatography (LC) combined with electrospray ionization-tandem mass spectrometry (ESI-MS/ MS) has been used as a method for the direct identification of multiple cytochrome P450 (P450) isoforms found in male and female rat liver. In this targeted proteomic approach, rat liver microsomes were subjected to sodium dodecyl sulfate-polyacrylamide gel electrophoresis followed by in-gel tryptic digestion of the proteins present in the 48-to 62-kDa bands. The resultant peptid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
1
1

Year Published

2004
2004
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 36 publications
1
24
1
1
Order By: Relevance
“…48 Several efforts to discriminate between CYP isoforms by proteomicsandmassspectrometryaredescribedintheliterature. 15,[47][48][49][50][51][52][53] Most of the studies were performed with rat or mouse liver. But since the CYP pattern of these organisms is mainly different from that in human, studies are hardly comparable.…”
Section: Donormentioning
confidence: 99%
“…48 Several efforts to discriminate between CYP isoforms by proteomicsandmassspectrometryaredescribedintheliterature. 15,[47][48][49][50][51][52][53] Most of the studies were performed with rat or mouse liver. But since the CYP pattern of these organisms is mainly different from that in human, studies are hardly comparable.…”
Section: Donormentioning
confidence: 99%
“…Previously we have demonstrated the use of SDS-PAGE in combination with reversed phase LC coupled to electrospray (ES) MS/MS for the identification of multiple P450 proteins (16,17). One of the main advantages of this approach is the molecular mass-based separation provided by SDS-PAGE, which allows proteins only from the molecular mass region of the P450s to be selected for analysis.…”
mentioning
confidence: 99%
“…Rat liver microsomes were obtained from untreated male rats. Previously, it was shown that such microsomes do not contain CYP2B1 and CYP2B2 (Galeva and Altermann, 2002;Galeva et al, 2003;Nisar et al, 2004). Twenty micrograms of total microsomal protein were electrophoresed on 10% SDS-polyacrylamide gel.…”
Section: Resultsmentioning
confidence: 99%